2011
DOI: 10.3109/03009742.2011.562533
|View full text |Cite
|
Sign up to set email alerts
|

Reactive arthritis in a population exposed to an extensive waterborne gastroenteritis outbreak after sewage contamination in Pirkanmaa, Finland

Abstract: Taking into account the large population contaminated with potentially arthritogenic agents, the occurrence of ReA was rare and mild in character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
3
19
1
Order By: Relevance
“…This suggests the acute epidemic had no residual effects at a population level. Supporting evidence has been reported in regard of occurrence of reactive arthritis in this study area half a year after the incidence [23]. However, prior studies have shown that the effects of gastroenteritis from drinking water contaminated with Campylobacter may materialize later -with a delay of up to fifteen years- as increase in arthritis symptoms or inflammatory bowel disease [10], [15], [24], or in case of Giardia infection as functional gastrointestinal diseases [12].…”
Section: Discussionsupporting
confidence: 74%
“…This suggests the acute epidemic had no residual effects at a population level. Supporting evidence has been reported in regard of occurrence of reactive arthritis in this study area half a year after the incidence [23]. However, prior studies have shown that the effects of gastroenteritis from drinking water contaminated with Campylobacter may materialize later -with a delay of up to fifteen years- as increase in arthritis symptoms or inflammatory bowel disease [10], [15], [24], or in case of Giardia infection as functional gastrointestinal diseases [12].…”
Section: Discussionsupporting
confidence: 74%
“…IL23 responses have been suggested to be enhanced in AS owing to altered micro bial composition of the gut. 56,57 Unlike reactive arthri tis, which can be triggered by gastro intestinal infection with Salmonella, Shigella, Yersinia or Campylobacter species, 58 AS does not seem to have an obvious infectious trigger. Instead, subtle alterations in the gut microbial commu nity (microbiome) might have an important role in AS pathogenesis.…”
Section: Progress In Non-mhc Geneticsmentioning
confidence: 99%
“…Between 5% and 10% of patients with AS develop clinically diagnosed inflammatory bowel disease (IBD), and a further 70% of patients with AS develop subclinical gut inflammation [1,2]. In reactive arthritis, a member of the SpA family, inflammatory arthritis develops following urogenital infection with Chlamydia trachomatis or gastrointestinal infection with Campylobacter, Salmonella, Shigella, or Yersinia [3]. Such cause-and-effect relationships are not established for other SpAs.…”
Section: Ankylosing Spondylitismentioning
confidence: 99%